Long term experience of gamma knife radiosurgery for benign skull base meningiomas. Issue 10 (16th September 2005) - Kreil, W; Luggin, J; Fuchs, I; Weigl, V; Eustacchio, S; Papaefthymiou, G
Abstract : Objectives: As most reports on the gamma knife have related only to short or mid-term results, we decided to evaluate the effectiveness and toxicity of radiosurgical treatment for benign skull base meningiomas in 200 patients with a follow up of 5–12 years to define the role of gamma knife radiosurgery (GKRS) for basal meningiomas and to provide further data for comparison with other treatment options. Methods: In total, 99 patients were treated with a combination of microsurgical resection and GKRS. In 101 patients, GKRS was performed as the sole treatment option. Tumour volumes ranged from 0.38 to 89.8 cm 3 (median 6.5 cm 3 ), and doses of 7–25 Gy (median 12 Gy) were given to the tumour borders at covering isodose volume curves (range 20–80%, median 45%). Results: The actuarial progression free survival rate was 98.5% at 5 years and 97.2% at 10 years. Passing radiation induced oedema occurred in two patients (1%). The neurological status improved in 83 cases (41.5%), remained unaltered in 108 (54%), and deteriorated in 9 (4.5%). Worsening was transient in seven patients (3.5%) and unrelated to tumour or treatment in one (0.5%). Repeated microsurgical resection was performed in five patients following GKRS (2.5%). Conclusions: GKRS has proved to be an effective alternative to microsurgical resection, radiotherapy, and Linac based radiosurgery for adjunctive and primary treatment of selected patients with basal meningiomas. Because of the excellent long term tumour control rate and low morbidity associated with GKRS, this treatment option should be used more frequently in the therapeutic management of benign skull base meningiomas.